The dark side of Thomas Jefferson: Legal education, natural rights and jus positivism (1760-1779) - Pinheiro, Marcos Sorrilha [UNESP] (My University, 2020)
Thomas Jefferson is the founding father with greatest recognition outside the USA. This is because his name is directly linked to the Declaration of Independence. This correlation makes that all the meanings attributed to this document, as being one of the forerunners of Human Rights, lend to its author those same qualities. Because of this, Jefferson is credited with a jus naturalist conception of rights. Facing this scenario, this article offers an alternative view of this character, starting from the hypothesis that his legal education contributed to his adherence to a pragmatic conception about human beings and their rights, seeing in the positive laws a greater power than the rights created by the nature’s God. This interpretation allows us to get new perspectives on some of his writings as: Summary view of the rights of Britsh America (1774), Declaration of Independence (1776) and Bill for establishing religious freedom (1779).
O lado sombrio de Thomas Jefferson: Formação jurídica, direitos naturais e jus positivismo (1760-1779)
Keywords: Jus positivism; Natural rights; Thomas Jefferson (1743-1826)